The Effect of Differentiated Learning Implementation on Learning Motivation and Student Learning Outcomes of SMA Negeri 1 Poto Tano - Rohyanti, Sari Dewi; Suparman, Suparman; Anggara, Mietra (JUPE : Jurnal Pendidikan Mandala, 2023)
There are two objectives of this study, first, to explain how the strategy of implementing differentiated learning to improve students' motivation and learning outcomes in Biology subjects in class XI students at SMA Negeri 1 Poto Tano. Second, to analyze how the effect of the application of differentiated learning on student motivation and learning outcomes in biology subjects in class XI students of SMA Negeri 1 Poto Tano. The type of research used in this study is quantitative research with experimental methods. The subjects in this study were all students of class XI-2 as many as 33 people who acted as an experimental class and XI-3 as many as 31 students who acted as a control class. The instruments used in this study were learning outcome tests and student learning motivation questionnaires. The results of data analysis obtained that the significance value < t, namely (0.000 < 0.05), then there is a significant effect in the motivation and learning outcomes of students in biology subjects between the group that applies differentiated learning (experimental group) and the group that applies conventional learning (control group) at SMA Negeri 1 Poto Tano.